Penerapan Metode Pembobotan LOPCOW dan Grey Relational Analysis Dalam Penentuan Pemasok Toserba Terbaik - Izka, Ade Adyatna; Sulistiani, Heni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Selecting the best supplier is a crucial aspect in the supply chain that has a significant impact on operational efficiency and final product quality. The main problem in this study is that there is no model in the selection of the best supplier that is carried out, but the company always assesses the performance of suppliers to see the performance of suppliers periodically and ensure that the agreed standards are still met and re-evaluate if necessary. This study combines the advantages of LOPCOW in objectively weighting criteria based on logarithmic percentage changes in data, with the strength of GRA in handling data complexity and uncertainty in multi-criteria evaluation. This combination improves the accuracy and reliability of decisions taken, as it combines the advantages of objectivity in weighting with strong analytical capabilities in alternative evaluations. The result is a more holistic, objective, and data-driven decision-making process, which is especially beneficial in complex and uncertain situations. The results of the ranking of the best convenience store suppliers show that Supplier AB is the first best with a value of 0.1722, Supplier JB is the second best with a value of 0.12, and MA Supplier is the third best with a value of 0.0848. The results of this study are recommendations for convenience stores in assessing the performance of existing suppliers.